Rebel without a cause [videorecording (Blu-Ray)] - Ray, Nicholas, 1911-1979; Dean, James, 1931-1955; Wood, Natalie; Mineo, Sal, 1939-1976 (Warner Bros. Entertainment, 2014)
When a rebellious young man with a troubled past moves to a new town, he makes both friends and enemies.